PENERAPAN METODE SUPPORT VECTOR MACHINE DALAM KLASIFIKASI INDEKS PEMBANGUNAN MANUSIA DI SUMATERA UTARA - Aulia Lia Yusharsah; Sajaratud Dur; Hendra Cipta (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The human development index in 2020 get slowdown in growth of 0.04%. The problem becaused per capita expenditure has decreased due to the COVID-19 pandemic. The purpose of this research is to implementation of a classification method used in the classification of the human development index in North Sumatra Province in 2020 and find out the accuracy value obtained. In implementation of support vector machine method with the Radial Basic Function (RBF) kernel function got the accuracy value is enough good at 79.31% with parametersC=1. The human development index in 2020 get slowdown in growth of 0.04%. The problem becaused per capita expenditure has decreased due to the COVID-19 pandemic. The purpose of this research is to implementation of a classification method used in the classification of the human development index in North Sumatra Province in 2020 and find out the accuracy value obtained. In implementation of support vector machine method with the Radial Basic Function (RBF) kernel function got the accuracy value is enough good at 79.31% with parametersC=1, .